2019
DOI: 10.1111/acem.13839
|View full text |Cite
|
Sign up to set email alerts
|

Video Discharge Instructions for Acute Otitis Media in Children: A Randomized Controlled Open‐label Trial

Abstract: Background Thirty percent of children with acute otitis media (AOM) experience symptoms < 7 days after initiating treatment, highlighting the importance of comprehensive discharge instructions. Methods We randomized caregivers of children 6 months to 17 years presenting to the emergency department (ED) with AOM to discharge instructions using a video on management of pain and fever to a paper handout. The primary outcome was the AOM Severity of Symptom (AOM‐SOS) score at 72 hours postdischarge. Secondary outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
0
4
0
3
Order By: Relevance
“…Alternatively, Wood [ 10 ] pointed out that the benefit of VDI depends on the disease, observing a greater improvement in caregivers’ knowledge when they received VDI for gastroenteritis than for fever/bronchiolitis. Although a single clinical trial regarding acute media otitis found no differences between paper and video instructions [ 18 ], most studies [ 3 , 10 12 ] agree that VDI minimize factors which affect the comprehension of the instructions such as the communication skills of healthcare providers. Our results prove that video instructions do not add extra time to the emergency department visits, as already suggested by previous articles [ 3 ] .…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, Wood [ 10 ] pointed out that the benefit of VDI depends on the disease, observing a greater improvement in caregivers’ knowledge when they received VDI for gastroenteritis than for fever/bronchiolitis. Although a single clinical trial regarding acute media otitis found no differences between paper and video instructions [ 18 ], most studies [ 3 , 10 12 ] agree that VDI minimize factors which affect the comprehension of the instructions such as the communication skills of healthcare providers. Our results prove that video instructions do not add extra time to the emergency department visits, as already suggested by previous articles [ 3 ] .…”
Section: Discussionmentioning
confidence: 99%
“…Whereas Wood et al 30 demonstrate the effectiveness of tailoring discharge instructions with video to improve knowledge for Spanish-speaking caregivers, other recently published evidence does not support the view that general video discharge instructions for acute otitis media, for example, increase caregiver knowledge. 31 Furthermore, in this issue of JEN, Leclerc 12 identifies the culturally contextual and relevant need for emergency nursing education in caring for indigenous patients. Finally, the adoption domain in the RE-AIM Framework includes an evaluation of who delivered the intervention.…”
Section: In This Issuementioning
confidence: 99%
“…There are some examples in the international literature of using application-based and video-based methods for providing discharge communication from hospital to patients or caregivers. These include application-based discharge communication to assist stroke patients after hospital discharge (Siegel et al 2016), provision of audiovisual discharge instructions on pain and fever management to caregivers for acute otitis media in children (Belisle et al 2019) and provision of audio-visual discharge instructions to general medical inpatients on discharge (Newnham et al 2015). This scoping review did not identify any novel methods of communicating discharge information from hospitals to GPs in the Australian context.…”
Section: Summary Of Evidencementioning
confidence: 98%